2016
DOI: 10.1007/s00449-016-1572-2
|View full text |Cite
|
Sign up to set email alerts
|

Cell growth stimulating effect of Ganoderma lucidum spores and their potential application for Chinese hamster ovary K1 cell cultivation

Abstract: In this work, water-soluble extracts of Ganoderma lucidum spores (Gls), a Chinese medicinal herb that possesses cell growth stimulating function, were found to be an effective growth factor for Chinese hamster ovary (CHO) cell cultivation. The Gls extract was prepared and supplemented to CHO K1 cell culture media with various serum levels. Our results obtained from both the static culture and the spinner-flask suspension culture showed that use of small-amount Gls extract effectively promoted cell growth and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies using low serum and serum-free medium for cell culture have shown that low fetal bovine serum contains fewer risk components and requires less time, labor, and laboratory space for expanding cells. However, compared with animal component-free medium, the use of low serum medium in clinical applications will still bring many uncertain risks [ 59 , 60 ]. Additionally, the hDPSCs/hTDM complexes cultured in the three media all regenerated dentin-like, pulp-like, and fibrous-like tissue, according to histomorphological analysis of our study, which indicated that ACF medium can substitute SCM for the pre-transplantation culture of hDPSCs/hTDM complexes in tissue engineering of bioengineered-root regeneration in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using low serum and serum-free medium for cell culture have shown that low fetal bovine serum contains fewer risk components and requires less time, labor, and laboratory space for expanding cells. However, compared with animal component-free medium, the use of low serum medium in clinical applications will still bring many uncertain risks [ 59 , 60 ]. Additionally, the hDPSCs/hTDM complexes cultured in the three media all regenerated dentin-like, pulp-like, and fibrous-like tissue, according to histomorphological analysis of our study, which indicated that ACF medium can substitute SCM for the pre-transplantation culture of hDPSCs/hTDM complexes in tissue engineering of bioengineered-root regeneration in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…G. lucidum spores are microscopic and are ejected from the cap during growth and maturation. These germ cells have all of G. lucidum genetically active substances [8]. Modern pharmacological studies have shown that G. lucidum spores have antitumor effects, increase immune regulation, lower blood sugar and lipid, increase anti-inflammatory and antihypoxia ability, and scavenge free radicals [9].…”
Section: Introductionmentioning
confidence: 99%